The role of the CLL-1 protein in disease monitoring in patients diagnosed with acute myeloid leukaemia and myelodysplastic syndrome - Ewa Dobak; Sylwia Romana Jankowska-Szabłowska; Renata Guzicka-Kazimierczak; Paulina Poter; Elżbieta Urasińska; Katarzyna Karpińska-Łukaszewicz (Polish Journal of Pathology)
The normal subpopulation of CD34+CD38 – haematopoietic stem cells does not express CLL-1; therefore, the assessment of the expression of this protein can be used for the diagnosis of minimal residual disease. The aim of this study was to evaluate, using multi-colour flow cytometry, the level of CLL-1 protein expression on CD34+CD38- myeloid niche cells in acute myeloid leukaemia (AML) and myelodysplastic syndromepatients at the time of diagnosis and during disease monitoring on the example of 3 practical cases. The following conclusion was drawn: CD34+CD38-CLL-1+ cells in AML patients may serve as a biomarker to predict disease aggressiveness.